The use of the FIFA 11+ For Kids as an injury prevention program in youth soccer players: A critically appraised topic - Osumi, K.; Kuehner-Boyer, C. (International Journal of Athletic Therapy & Training, 2025)
The FIFA 11+ For Kids was developed as an injury prevention program for youth soccer athletes between 7 and 13 years of age. Since its development, it has been introduced to youth soccer players worldwide, however, a critical summary of high-level randomized control trials to assist clinicians in determining how to effectively implement the program for injury prevention is lacking in the current literature. This critically appraised topic sought to determine the best practice recommendations for the implementation of the FIFA 11+ For Kids program to effectively prevent injuries in youth soccer players. A search of the literature was completed in December of 2023 using the terms "FIFA 11 for kids" and "randomized control trials" and "injury prevention." Studies were included if they scored higher than 6/10 on the Physiotherapy Evidence Database Scale. A critical appraisal of high-level randomized control trials found that clinicians can use the FIFA 11+ For Kids as an effective injury prevention program for youth soccer players when factors including the frequency of application, the time needed to complete the program, compliance with the program, and training of team personal who lead the program are considered.